HỖ VĂN” (INTERTEXTUAL ELEMENT) IN ANCIENT CHINESE AND SOME CONSIDERATIONS IN TRANSLATING INTO VIETNAMESE (Journal of Foreign Language Studies, 2024)
“Hỗ văn” (intertextual element) in Ancient Chinese, referred to under different names, is a rhetorical device used in the writing of literature. It is relatively special despite its rare appearance in Ancient Chinese. On the basis of Chinese scholars’ research studies, this article aims to introduce, analyse and summarize the definitions, forms and characteristics of auxiliary. It also points out some considerations in translating sentences with ““hỗ văn” (intertextual element)” in order to enhance the quality of the Vietnamese translations.
Keywords: intertextual element; Ancient Chinese; translation